Political philosophy beyond methodological nationalism. Issue 2 (19th January 2021) - Sager, Alex
Abstract: Interdisciplinary work on the nature of borders and society has enriched and complicated our understanding of democracy, community, distributive justice, and migration. It reveals the cognitive bias of methodological nationalism, which has distorted normative political thought on these topics, uncritically and often unconsciously adapting and reifying state‐centered conceptions of territory, space, and community. Under methodological nationalism, state territories demarcate the boundaries of the political; society is conceived as composed of immobile, culturally homogenous citizens, each belonging to one and only one state; and the distribution of goods is analyzed according to a stark opposition between the domestic and the international. This article describes how methodological nationalism has shaped central debates in political philosophy and introduces recent work that helps dispel this bias.